Tinospora cordifolia protects from skeletal muscle atrophy by alleviating oxidative stress and inflammation induced by sciatic denervation. (23rd May 2020) - Sharma, Bhawana; Dutt, Vikas; Kaur, Nirmaljeet; Mittal, Ashwani; Dabur, Rajesh
Abstract: Ethanopharmacological relevance: Tinospora cordifolia ( TC ) is widely being used as immunomodulatory and re-juvenile drug and well described in Indian Ayurveda system of medicine. Rejuvenation also means the fine tuning of the skeletal muscles. Skeletal muscle related disorder, i.e. atrophy is major problem which arise due to cachexia, sarcopenia and immobilization. However, despite of the great efforts, there is scarcity of FDA approved drugs in the market to treat skeletal muscle atrophy. Aim of the study: The current study was aimed to explore the in-vitro and in-vivo efficacy and mechanism of TC in myogenic differentiation and skeletal muscle atrophy to establish the possibility of its usage to counteract skeletal muscle atrophy. Materials and methods: C2C12 cell lines were used to determine myogenic potential and anti-atrophic effects of T. cordifolia water extract ( TCE ). Its in-vitro efficacy was re-validated in vivo by supplementation of TCE at a dose of 200 mg/kg/p.o. for 30 days in denervated mice model of skeletal muscle atrophy. Effects of TCE administration on levels of oxidative stress, inflammatory markers and proteolysis were determined. Results: TCE supplementation displayed increased lymphocyte proliferation and induced myogenic differentiation of C2C12 myoblasts by significantly increasing myocytes length and thickness, in comparison to control (p < 0.05). TCE supplementation decreased oxidative stress and inflammatory response by significantly modulating activities of catalase, glutathione peroxidase, lipid peroxidase, superoxide dismutase and β-glucuronidase (p < 0.05). It increased MF-20c expression and ameliorated degradation of muscle protein by down-regulating MuRF-1 and calpain activity. Conclusion: TCE supplementation promotes myogenic differentiation in C2C12 cell lines and prevents denervation induced skeletal muscle atrophy by antagonizing the proteolytic systems (calpain and UPS) and maintaining the oxidative defense mechanism of the cell. Hence, TCE can be used as a protective agent against muscle atrophy. Graphical abstract: Image 1 Highlights: Water extract of T. cordifolia ( TCE ) boosted up in vitro myogenic differentiation. TCE supplementation also prevented atrophy in C2C12 myoblasts induced by TNF-α. In vivo TCE treatment decreased oxidative stress and inflammation in atrophic model. It antagonized calpain and ubiquitin proteolytic systems in denervation induced atrophy. TCE can be used as a protective agent against skeletal muscle atrophy.